ANALISIS KERJASAMA INDONESIA DAN UNI EMIRATE ARAB (UEA) DALAM BIDANG PERTAHANAN (2019-2021) - Ahmad Zainal Mustofa (Universitas Islam Darul Ulum Lamongan, 2021)
This article describes the cooperation relationship between Indonesia and the United Arab Emirates in the field of defense. This study uses a defense diplomacy approach. Then to describe the data sources using descriptive analytical research methods. The result of this research is that diplomatic relations between Indonesia and the United Arab Emirates have been ongoing since 1976. In 1978, Indonesia opened an embassy in Abu Dhabi. Then in 1991 the United Arab Emirates opened an embassy in Jakarta. Then the form of cooperation that exists between Indonesia and the United Arab Emirates is that PT Pindad and Caracal will work together to carry out joint production of various weapons, including the AR15-based CAR 816 assault rifle for use by special forces in Indonesia using the barrel component and other components from Pindad. Joint production of the Pindad SM3 5.56 mm machine gun for use by the UAE army and marketed in the Middle East, as well as the use of Pindad-made barrels and other weapons components for weapons made by Caracal. Thus, the two countries can strengthen state security by minimizing the budget for the main weapon system equipment by relying on private products in the context of bilateral cooperation.